259 Sinonasal Glomangiopericytoma: A Case Report of an Unusual Neoplasm With Emphasis on the Differential Diagnosis. (11th January 2018) - Kassaby, Sarah; Patterson, Emily
Abstract: Sinonasal glomangiopericytoma is a rare benign tumor arising from the pericytes surrounding capillaries and accounts for less than 0.5% of all sinonasal tumors. The etiology of this tumor is not clear, although trauma, hypertension, pregnancy, and corticosteroid use have been hypothesized. Clinically, sinonasal glomangiopericytoma tends to present as a mass causing nasal obstruction, chronic epistaxis, or facial pain. We report a case of a 71-year-old hypertensive man on anticoagulation who presented to the emergency room with a three-day history of uncontrolled epistaxis. Endoscopic control of epistaxis was attempted, and bleeding was noted from the left sphenoethmoid recess, without a discrete mass lesion. Biopsy from the area of bleeding revealed a neoplastic proliferation of uniform cells with fusiform contours, eosinophilic cytoplasm, and admixed hyalinized vascular channels. The neoplastic cells were positive for SMA, and negative for CD34, STAT6, ERG, caldesmon, keratin, desmin, MART1, and S100, supporting the diagnosis of sinonasal glomangiopericytoma. Glomangiopericytoma must be strictly differentiated from the soft tissue-type hemangiopericytoma as they represent two different entities histologically as well as clinically, with the latter showing a more aggressive behavior. The differential diagnosis of glomangiopericytoma includes glomus tumor, solitary fibrous tumor, cellular hemangioma, angiofibroma, and epithelioid tumors. Sinonasal glomangiopericytoma is categorized as a borderline/low malignant potential neoplasm showing an excellent overall prognosis after complete excision. However, follow-up is recommended due to risk of local recurrence/malignant transformation.